ANALYSIS OF TOMIKO CHARACTERS IN THE NOVEL NAMAKU HIROKO OF NH DINI WORK: LITERATURE SOCIOLOGY STUDY - Bunga Tisya; Yuliana Yuliana; Suaibatul Aslamiyah (Bahtera: Jurnal Pendidikan Bahasa dan Sastra, 2020)
Hiroko in the novel Namaku Horoko (‘My Name is Hiroko’) is the main character that is often discussed by many people. However, not many people know that the character Tomiko in this novel has a significat influence on the storyline. The purpose of this study was to analyze the character of Tomiko whose role is not less important than the main character. This study uses the novel Namaku Hiroko as a data source. The approach in this research is the sociology of literature approach. The research method used is descriptive qualitative. The results in this study are the great influence of Tomiko in the novel on the values ​​of life that prevailed in the 70s. In addition, Tomiko's character has a very important role to other figures. Because Tomiko's character gives a lot of help to several other figures who make their lives free from various social and economic problems told in the novel. Thus, this research shows that the role of Tomiko influences that there are social, cultural and economic gaps in people's lives and that these problems have become a habit and cannot be separated in the social life of the community.